Sterol synthesis pathway inhibition as a target for cancer treatment. (28th November 2020) - Feltrin, Sara; Ravera, Francesco; Traversone, Noemi; Ferrando, Lorenzo; Bedognetti, Davide; Ballestrero, Alberto; Zoppoli, Gabriele
Abstract: Sterol synthesis is a highly complex and integrated pathway in mammals. In the present review, we briefly summarize the main steps of this pathway, especially concerning its main rate-limiting enzymes, HMG-CoA reductase (HMGCR) and squalene epoxidase (SQLE), in relation with cancer. We focus on studies reporting key findings linking cholesterol with cancer. The inhibition of HMGCR and SQLE to prevent and inhibit cancer are reviewed. Finally, a pan-cancer review of publicly available data on genomic aberrations in the main enzymes involved in sterol biosynthesis and their transcription factors is reported, providing hitherto unexplored findings that may be the subject of future research in cancer metabolomics and tumor targeted treatment. Highlights: Cholesterol biosynthesis is disrupted in cancer. HMG-CoA reductase and squalene epoxidase are appealing targets for treatment in cancer. Pan-cancer analysis reveals unexpected aberrations in sterol biosynthesis enzymes.